Restor(y)ing meaning: reading Manoel de Oliveira’s Non ou a Vã Glória de Mandar - Gonçalves Miranda, Rui (Taylor & Francis, 2013)
Manoel de Oliveira’s Non ou a Vã Glória de Mandar (1990) is a landmark in Lusophone cinema’s revisitation of the history of Portuguese expansion and colonial conflicts. This article aims at analysing the film’s political import by extrapolating from Jacques Rancière’s meditation on the ‘aesthetic regime’ and from Manoel de Oliveira’s references to Derridean deconstruction. Non and Oliveira’s filming praxis both exceed and disrupt the filmmaker’s personal logocentric and teleological theories of history and cinema.